A Useful Maneuver to Install Pneumoperitoneum for Laparoscopy in a Frozen Abdomen: Case Report - Munive, Angel Martínez; Rosenthalc, Jareth Lassard; Gómez, María Sofía Tron; García, Dr. Jorge Cueto (Jour Med Resh and Health Sci, 2022)
Introduction The presence of massive intraperitoneal adhesions known as frozen abdomen is a feared complication generated by multiple laparotomies and/or severe acute and chronic inflammatory processes. To prevent organ damage due to the adhesive process surgeons must use nontraditional approaches to install safely the pneumoperitoneum if a laparoscopic procedure has been chosen. Material and Methods A 44-year-old man underwent 2 emergency open laparotomies in 1999 after receiving 2 gunshot wounds and later, had a laparotomy and a colostomy closure with a satisfactory recovery. Results Nineteen years later he presented with subacute cholecystitis and an alternate right flank incision was made to install the pneumoperitoneum and a laparoscopic cholecystectomy was performed without incidents. Discussion The “blind” right flank puncture was successful, a limited pneumoperitoneum was created following which a laparoscopic cholecystectomy was carried out after an extensive lysis of adhesions.